(untitled) (Vietnam Journal of Community Medicine, 2026)
Objective: To evaluate the results of treatment of closed supracondylar humeral fractures in children by traction and plaster cast at Viet Duc Friendship Hospital from May 2025 to July 2025. Subjects and methods: A cross-sectional descriptive study on 56 children with supracondylar humeral fractures treated by traction and plaster cast at Viet Duc Friendship Hospital from May 2025 to July 2025. Results: The most common age group is 6-10 years old, boys are more common than girls with a ratio of 2/1. Common clinical symptoms in order are pain (100%), decreased and loss of function (94.6%), swelling and bruising (91.1%), and limb axis deviation (82.1%). The most common Gartland classification is grade II - III. After 1 month, all children have grade 2 or higher bone calcification. After 3 months, the results were very good (46.4%), good (41.1%), average (7.1%), and poor (5.4%). Conclusion: This method is very effective, easy to perform, and is the first and safe choice in treating supracondylar humeral fractures in children.